O advento do niilismo como desmoronamento dos supremos valores no pensamento de Friedrich Nietzsche - Leite, Joseph Anderson Ponte Cavalcante (2016)
From the hermeneutic reading of some texts of the German philosopher Friedrich Nietzsche, as well as some commentators of his thoughts, we have to researched object to what the Nietzschean philosophy says about nihilism, theme that awakened in Nietzsche a unique and extraordinary attention. To fulfill this research, we will have as main research corpus that is the posthumous fragment 11 [99], which expresses the nihilism as a movement that becomes present on the rise from the collapse of the events of supreme values; presented here as the three categories of reason, such as goal, unity and truth. Thus, it is necessary to focus on understanding the meaning of the value cathagory for Nietzsche and, also, to evince the link between the act of valuation and the movement of nihilism, paying attention to another important element that surrounds the Nietzschean philosophy: the perspectivism. Moreover, in order to investigate about nihilism and everything that surrounds it as event, it is necessary to point to the fundamental principle in which Nietzsche names the real aspect, the will to power in its eternal returning. As a principle of what engenders value and the dynamics of life, it is imperative, then, point to the will to power as that which governs the reality, not as essence or substance, but as something that insist on returning to constitute, as which insists on returning with eagerness for power.